The use of recombinant activated factor VII in patients with acquired haemophilia. (June 2015) - Tiede, Andreas; Amano, Kagehiro; Ma, Alice; Arkhammar, Per; el Fegoun, Soraya Benchikh; Rosholm, Anders; Seremetis, Stephanie; Baudo, Francesco
Abstract: Acquired haemophilia (AH) is a rare, often severe bleeding disorder characterised by autoantibodies to coagulation factor VIII (FVIII). Observational studies offer crucial insight into the disease and its treatment. Recombinant activated factor VII (rFVIIa, eptacog alfa activated) was available on an emergency and compassionate use basis from 1988 to 1999 at sites in Europe and North America. In 1996, rFVIIa was approved in Europe for the treatment of AH; it was licensed for this indication in the United States in 2006. Recombinant activated FVII is approved for first-line treatment of bleeding episodes and prevention of bleeding in surgical/invasive procedures in patients with AH. This review provides an up-to-date summary of the haemostatic efficacy of rFVIIa in patients with AH, from the first emergency and compassionate use programmes, to patient registries and a post-marketing surveillance study. In acute bleeding episodes, rFVIIa provided high and consistent rates of control, and available data showed that acute bleed control rates were higher for first-line rFVIIa versus salvage rFVIIa. In surgical procedures, rFVIIa also provided high rates of control. In patients with AH, rFVIIa has a high rate of haemostatic efficacy in acute and surgical bleeding episodes.